FEATURES OF MANAGING THE PROCESS OF FORMING A FAVORABLE SOCIAL AND PSYCHOLOGICAL CLIMATE IN THE TEAM OF A MODERN ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The practice of modern enterprises shows that a favorable social and psychological climate in the team increases the efficiency of the enterprise, contributes to reducing staff turnover and improving the general atmosphere at the workplace. At the same time, knowledge of the features of the effective formation of the appropriate social and psychological climate allows managers to create conditions for the professional and personal development of personnel, which results in an increase in the effectiveness of the enterprise.The purpose of the article. The purpose of the article is to study the specifics of managing the formation of the appropriate social and psychological climate in the workforce of modern enterprises for the development of recommendations for an effective personnel management strategy.Methods. The research methodology is based on the analysis of scientific literature and empirical studies in the field of human resource management, organizational psychology and sociology. Such methods of scientific knowledge as the method of analysis and synthesis, comparison, and abstraction were also used. Such a comprehensive approach made it possible to understand not only the theoretical aspects of climate management in the team, but also the practical methods of its implementation in a real business environment.Results. The article considers the key aspects of managing the formation of a favorable social and psychological climate in the collective of a modern enterprise. The key factors affecting the formation of a positive working environment are considered. Various aspects of the impact of organizational culture on the formation of a favorable working environment have been studied. The importance of effective communication between management and staff, as well as between employees, is highlighted in order to create trusting relationships and promote collective success. Different leadership styles and their impact on staff morale and motivation are analyzed. The importance of effective conflict resolution at the workplace and the development of joint problem-solving strategies has been proven. The peculiarities of the application of these approaches in ensuring sustainable growth and competitiveness of enterprises in the modern business environment are studied.Conclusions. Based on the analysis of key aspects of organizational culture, communication practices, leadership and conflict management, practical approaches to the formation of a favorable social and psychological climate in the company's team have been determined. Specific practical methods are proposed for increasing employee satisfaction, reducing staff turnover and increasing labor productivity, which contributes to the sustainable development of the enterprise in the conditions of modern business.
Keywords: personnel management, psychology of management, staff satisfaction, socio-psychological climate, labor productivity, the workforce of the enterprise, employment, labor potential, labor market.